Socioeconomic status, social relations and domestic violence (DV) against elderly people in Canada, Albania, Colombia and Brazil. Issue 3 (May 2015) - Guedes, Dimitri Taurino; Alvarado, Beatriz Eugenia; Phillips, Susan P.; Curcio, Carmen Lucia; Zunzunegui, María Victoria; Guerra, Ricardo Oliveira
Highlights DV is an important issue for elderly people. Violence varies according to living/health conditions of elderly people. Women are more victimized than men, but this merits further investigation. Poor support from partner/family is an indicator of conflict leading to violence.